Impact of Pals1 on Expression and Localization of Transporters Belonging to the Solute Carrier Family - Berghaus, Carmen; Groh, Ann-Christin; Breljak, Davorka; Ciarimboli, Giuliano; Sabolić, Ivan; Pavenstädt, Hermann; Weide, Thomas (Frontiers in Molecular Biosciences, 2022)
Pals1 is part of the evolutionary conserved Crumbs polarity complex and plays a key role in two processes, the formation of apicobasal polarity and the establishment of cell-cell contacts. In the human kidney, up to 1.5 million nephrons control blood filtration, as well as resorption and recycling of inorganic and organic ions, sugars, amino acids, peptides, vitamins, water and further metabolites of endogenous and exogenous origin. All nephron segments consist of polarized cells and express high levels of Pals1. Mice that are functionally haploid for Pals1 develop a lethal phenotype, accompanied by heavy proteinuria and the formation of renal cysts. However, on a cellular level, it is still unclear if reduced cell polarization, incomplete cell-cell contact formation, or an altered Pals1-dependent gene expression accounts for the renal phenotype. To address this, we analyzed the transcriptomes of Pals1-haploinsufficient kidneys and the littermate controls by gene set enrichment analysis. Our data elucidated a direct correlation between TGFβ pathway activation and the downregulation of more than 100 members of the solute carrier (SLC) gene family. Surprisingly, Pals1-depleted nephrons keep the SLC’s segment-specific expression and subcellular distribution, demonstrating that the phenotype is not mainly due to dysfunctional apicobasal cell polarization of renal epithelia. Our data may provide first hints that SLCs may act as modulating factors for renal cyst formation.